Study of cocaine seizures through spatial analysis (Research, Society and Development, 2021)
Cocaine trafficking and consumption continues to prosper despite the public policies that are in force in Brazil, despite its use for thousands of years, it is currently a public health problem. This study aimed to report the sociodemographic variables of individuals apprehended with cocaine and who were framed in Law n°. 11,343 of August 2006, in the municipality of Campina Grande, in 2017. It was a hybrid study, with a transversal, retrospective cut and ecological, with a quantitative approach. The neighborhood area variable was distributed in thematic maps and the spatial autocorrelation was measured by the Moran Global and Local indexes, which quantify the degree of autocorrelation. 210 cocaine seizures were recorded, of which 146 occurred in the municipality of Campina Grande, of these, only 94 presented all the data and were considered in this study. The months of September (n = 14) and October (n = 13) had the highest records of seizures. As for the pattern of use, crack in the yellowish stone form was predominant (n = 46), followed by cocaine hydrochloride in the form of white powder (n = 40). The profile of the individual apprehended with cocaine in the municipality was that of a young, single, unemployed and with low level of education. The predominant framework was drug trafficking (n = 75) according to Article nº. 33 of Law nº. 11,343 / 2006. The neighborhoods that registered the highest number of seizures were José Pinheiro (n = 15) and Pedregal (n = 8). The Moran General and Local indexis (p> 0.05), did not show spatial dependence between neighboring neighborhoods, that is, there is no autocorrelation for the analyzed variable.